Instrumentalizacja, programocentryzm, uprzedmiotowienie dziecka jako niedostatek polskiej edukacji - Sadowska, Katarzyna Bożena (Pedagogika Społeczna Nova, 2024)
The aim of the study is to draw attention to the excessive instrumentalisation, program-centrism and excessive didacticism of Polish child education system, which results in maintaining the tradition of monologue education and objectifying the child both in the nursery, kindergarten and at the early school education stage. The text also considers the difficulties found in the environment of carers, teachers and parents in perceiving not only key concepts for pedagogy such as: education, upbringing, teaching, learning or care, but also commonly used methodological solutions that result in significant impoverish- ment of the process of supporting the child’s development, making it almost exclusively a reproducer of knowledge artificially mediated by an adult. The author based on the principle of origin, assuming that the sources are scientific publications and legal acts as well as conversations with teachers.